Asymbiotic seed germination and in vitro seedling development of Orchis militaris, an endangered orchid in Siberia - Aleksandra Yurievna Nabieva (Journal of Genetic Engineering and Biotechnology, 2021)
Abstract Background Terrestrial orchids belonging to the Orchis genus are difficult to propagate and are under great pressure in their natural habitats. Studies regarding the influence of photoperiod and temperature regimes on Orchis militaris germination and morphological changes during immature seed development in vitro are scarce. Our aim was to identify photoperiod, temperature, and different nutrient media requirements for optimization of O. militaris seed germination and vigorous seedling production. Results Post-germination morphological changes were recorded with O. militaris seeds collected from 32-day-old fruits, where the percentage of O. militaris seeds without embryo was 38.4%. The highest rate of O. militaris seed germination (82.6%) was obtained on Malmgren modified terrestrial orchid medium (mM), enriched by 5% coconut water, 5% birch sap, and 0.1% AC. Nine percent of seedlings were able to reach the advanced seedling stage (stage 6) after 12 months of maintenance on this medium. In all 3 modified media (Harvais, Knudson С and Malmgren), regeneration was via the production of protocorms and seedlings without callus formation. It was proved that more abundantly vigorous protocorms were formed on the modified Harvais 2 under continuous darkness, while the subculture in Knudson C medium with AC addition could be necessary to stimulate their further development. The regeneration success of the species for in vitro conditions was increased by following its natural seasonal cycle. Conclusion This study demonstrated an efficient micropropagation system for O. militaris using immature seeds and thus widely opened the perspectives for its conservation in nature. The favorable conditions of seed germination periods for in vitro culture, identified as the definite shift of temperatures and photoperiod regimes intrinsic to the species in nature, could improve seedling survival of this medicinally important orchid.